CATS AND JAPANESE IDIOMATIC EXPRESSIONS RELATED TO CATS AND THEIR BACKGROUND - Rina Koike (International Journal of Literature and Language Studies, 2026)
Taking up cats, which have been kept as pets since ancient times in Japan, we study the origin of the name "cat" and also study, from a linguistic standpoint, idioms and proverbs including a word "cat" that have arisen and been used in relations between humans and cats. We investigate the function of particles " wa " and " ga " in idioms and proverbs that have "cat" as a subjective word. We also investigate their function in relation to the subjective word in idioms and proverbs that have "cat" as an objective word. Based on these considerations, we try to understand that the meaning of idioms and proverbs including a word "cat" can be determined in relations between humans and cats from ancient times to modern times.